Optimalisasi Program Keluarga Berencana, Keluarga Sakinah, dan Pasangan di Bawah Umur Lampung Timur - Siradjuddin, Azmi; Lumbu, Aliyandi A.; Fitria, Yuli (JOM, 2024)
Establishing a harmonious family (keluarga sakinah) for underage couples presents significant challenges, particularly due to their psychological immaturity, financial instability, and social pressures. This study aims to analyze the effectiveness of the Family Planning Program (KB) in assisting underage couples in Banjarrejo Village, Lampung Timur, in achieving a harmonious family. Using a descriptive qualitative method and an empirical case study approach, data were collected through interviews and observations of underage couples and Family Planning program administrators. The findings indicate that while the KB program has been implemented effectively in the village, its efficacy in preventing pregnancy for some couples remains suboptimal, as some still experienced pregnancy despite using the program. From the perspective of Islamic Family Law, the KB program is not in conflict with religious moral principles but is rather viewed as a means of supporting the formation of a harmonious, loving, and compassionate family (sakinah, mawaddah, warahmah), especially for underage couples facing unique challenges in achieving family welfare.